Uso de nanoemulsões de óleos essenciais no controle de Clostridium sporogenes em mortadela - Pinelli, Juliana Junqueira (2018)
The aim of this work was to evaluate the antimicrobial activity of essential oils combinations of cinnamon, lemon, oregano, cardamom and Chinese pepper and of nanoemulsions based on these combinations in the control of Clostridium sporogenes inoculated in mortadella and its influence on the technological characteristics of the product. The minimum bactericidal concentration (CMB) of each oil was determined using the broth dilution method. The CMB found were: 0,05% for the oregano essential oil; 0,10% for cinnamon essential oil and Chinese pepper essential oil; and 1,00% for lemon essential oil and cardamom essential oil. Microbiological analyzes of mortadella were performed for 20 days, with a 5 day interval for each analysis, with storage at 14°C.The technological analyses (physical-chemical) were performed after 1, 21 and 30 days of processing, under storage at 4°C.The pH, residual nitrite, lipid oxidation, water activity and color of five treatments were evaluated: control (75 ppm nitrite); Treatment 1 (75 ppm nitrite, 0,115% lemon essential oil, 0,115% cardamom essential oil, 0,0025% Chinese pepper essential oil); Treatment 2 (75 ppm nitrite, 0,015% cinnamon essential oil, 0,24% cardamom essential oil, 0,015% Chinese pepper essential oil); Treatment 3 (75 ppm nitrite + nanoemulsion consisting of 0,0225% Chinese pepper essential oil, 1,035% cardamom essential oil, 1,035% lemon essential oil); Treatment 4 (75 ppm nitrite + nanoemulsion consisting of 1,8% cardamom essential oil, 0,1125% Chinese pepper essential oil, 0,1125% cinnamon essential oil).Treatment 3 promoted a greater reduction of C.sporogenes vegetative cells in mortadella.The combinations of essential oils used did not prevent sporulation.Regarding the technological characteristics, no significant changes were observed between treatments. It was observed an increase in water activity and red index (a *) and a decrease in the hue angle (H *) and residual nitrite in the mortadellas only with the storage period, with the essential oils not having a significant influence on these parameters.The use of essential oils as natural preservatives in mortadella can be considered a promising alternative to the partial substitution of chemical preservatives, since the treatments with essential oils presented greater antimicrobial activities without altering the physical-chemical characteristics of the product.